Self-presentation as a problem field in psychology: review of classical and modern research - Fofanova, Galina A.; Aliakseyeva, Lizaveta A. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The result of the analysis of classical and modern scientific research of the phenomenon of self-presentation is presented. It is established that, despite a large amount of research in foreign and domestic psychology, there is still no single definition of this phenomenon. It is determined that due to the influence of the realities of modern life, in particular digitalisation, on the possibilities, strategies, and tactics of self-presentational behaviour, there is a need for a deep empirical study of digital self-presentation, which is of great importance in personal, professional, and government decision-making.